Bilateral Teleoperation of Wheeled Mobile Robots Working in Common Workspace - Lorinc Marton Marton; Zoltan Szanto; Piroska Haller; Hunor Sandor; Tamas Szabo; Tamas Vajda (Institute of Advanced Engineering and Science, 2014)
This paper proposes a bilateral control framework for mobile robots which share the same workspace. The robots are teleoperated by independent users. Accordingly, for each teleoperated robot the other robots represent moving obstacles or static obstacles with a-priori unknown positions. For such teleoperation systems a velocity generator algorithm is proposed to obtain the linear and angular velocity commands of the mobile robots. A procedure is also given to calculate the haptic force corresponding to each mobile robot. To guarantee the stability of the teleoperation in the presence of large communication delays, a supervisor control algorithm is proposed which constantly monitors the stability of the teleoperation system. Experimental measurements are provided to show the effectiveness of the proposed bilateral teleoperation strategy.